The possibility of registration of the colour per se - Carvalho, Maria Miguel (2014)
The admissibility of colour registration per se has been discussed at great length. In opposition to this possibility, the valuation of the general interest in not unduly restricting the availability of colours for other operators in the market («depletion theory»), has been invoked, among other things. Nevertheless, in the current state of Community law the answer to this possibility seems to be affirmative, after the requirements of trade mark registration have been met. In this study we focused briefly on the main issues that arise in this area, in light of the Court of Justice of the European Union case law.